Persetujuan Tindakan Medis Dalam Anestesiologi dan Perawatan Intensif Tinjauan Teori Hukum dan Hak Pasien - Pirma Ivan Ricky Manurung; Sulyaprilawati Battri Siahaan; Abdul Rahman Maulana Siregar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Informed consent is an essential element in health services, including in the field of anesthesiology and intensive care, which have high risks and involve critical medical decisions. This study aims to analyze the procedures and implementation of informed consent for patients in the anesthesia and intensive care unit, highlighting the legal and ethical aspects of decision-making. A qualitative approach was used to evaluate patients' and families' understanding of the medical information provided, their rights in agreeing to or refusing medical treatment, and the role of doctors in ensuring that consent is given voluntarily and informatively. Data were obtained through in-depth interviews with health practitioners and a review of related legal and medical ethics literature. The results of the study indicate that the implementation of informed consent in the intensive care unit and anesthesiology unit often faces challenges due to the critical condition of the patient, time constraints, and the complexity of communication. Therefore, this study recommends strengthening communication policies and training for medical personnel to ensure that patient rights are met and medical actions can be carried out in accordance with applicable ethical and legal principles.